1999
DOI: 10.1021/ic990326c
|View full text |Cite
|
Sign up to set email alerts
|

“Axial-Bonding”-Type Hybrid Porphyrin Arrays:  Synthesis, Spectroscopy, Electrochemistry, and Singlet State Properties

Abstract: A series of phosphorus(V), germanium(IV), and tin(IV) porphyrin-based, "axial-bonding"-type hybrid trimers have been readily constructed by employing a new "building-block" approach. The approach is modular in nature, and it involves simple "inorganic" reactions such as axial bond formation of main group element containing porphyrins and insertion of metal/"metalloid" ions into the porphyrin cavity. The architecture of these arrays is such that, while a phosphorus(V), germanium(IV), or tin(IV) complex of meso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 74 publications
3
77
0
3
Order By: Relevance
“…[24][25][26] The high charge on the tin centre renders the porphyrin a relatively hard Lewis acid with selectivity for oxo ligands (phenols, carboxylic acids) over softer nitrogenous ligands in solution. [24][25][26][27][28][29][30][31] Importantly for this study, the inductive effect of the high charge on the metal makes tin(IV) porphyrins very stable to ring reduction. [32] In this respect, studies by Reddy and Maiya indicated that ET can occur from a phenolate ligand to the photoexcited porphyrin, the efficiency of which increases with the basicity of the phenolate.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The high charge on the tin centre renders the porphyrin a relatively hard Lewis acid with selectivity for oxo ligands (phenols, carboxylic acids) over softer nitrogenous ligands in solution. [24][25][26][27][28][29][30][31] Importantly for this study, the inductive effect of the high charge on the metal makes tin(IV) porphyrins very stable to ring reduction. [32] In this respect, studies by Reddy and Maiya indicated that ET can occur from a phenolate ligand to the photoexcited porphyrin, the efficiency of which increases with the basicity of the phenolate.…”
Section: Introductionmentioning
confidence: 99%
“…[23] В 1 Н ЯМР спектре комплекса 8 сигналы протонов имидазольного фрагмента субстрата сдвинуты в сильное поле, по сравнению с сигналами соответствующих протонов в спектре 4-(имидазол-1-ил)-фенола (Рису-нок 2а). Согласно литературным данным [11][12][13]24] и ре-зультатам собственных исследований [15,17] это является следствием экранирующего эффекта кольцевого тока тетрапиррольного макроцикла. Расположенные на значительном удалении от макроцикла протоны фенольного фрагмента субстрата не подвергаются влиянию этого фактора и проявляются в той же области, что и соответствующие протоны в спектре 4-(имидазол-1-ил)-фенола.…”
Section: результаты и их обсуждениеunclassified
“…Они предпочтительно связывают кислород содержащие лиганды (карбокси-латы и феноляты) и являются комплексами с транс-диаксиальной координацией ионных или нейтральных субстратов. [10][11][12][13][14] Относительно лабильные карбокси-латные комплексы порфиринатов Sn(IV) легко образу-ются при взаимодействии карбоновой кислоты с дигидроксипорфиринатом Sn(IV) [(OH) 2 SnP] в органи-ческих растворителях при комнатной температуре. Скорость процесса определяется кислотными свойст-вами органической кислоты.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Maiya and co-workers used tin(IV) porphyrins to axially connect other metalloporphyrins by Lewis base/ Lewis acid interactions [14,15]. Very recently, a tin(IV) porphyrin was used to interconnect two carboxy-functionalized fullerene moieties and the resulting porphyrin-fullerene complex showed strong interactions between its components [16].…”
Section: Introductionmentioning
confidence: 99%